An integrated process for Industrial effluent treatment and Biodiesel production using Microalgae - Krishna, Arjun R.; Dev, Lipin; V., Thankamani (Research in Biotechnology, 2012)
The present day necessities and requirements have emphasized the need for a renewable and alternate energy source is very high. Besides, the present day energy resources posse potential threat to the environment by emitting Greenhouse gases (GHGs) etc. An integrated process which involves a model of the wastewater High Rate Algal Ponds (HRAPs) near the industries and establishment of Biodiesel plants nearer to these ponds to produce algal biodiesel along with other byproducts is elucidated.Ã‚Â Wastewater HRAPs also help in sequestering the CO2 emitted by the industries and is used by the microalga for their photosynthesis in turn providing oxygen to the bacterial population which accumulates and degrades the toxic compounds present in the industrial effluents. This integrated process involving cheaper treatment of industrial effluents, production of algal biodiesel, accumulation of toxicÃ‚Â compounds, sequestration of CO2 and various other non-fuel applications contribute to an effective energy management system.